Metode Tongkat Berbicara (Talking Stick) dalam Pembelajaran Keterampilan Berbicara Menanggapi Cerita Pendek - Sibuea, Mawar Sri Wulan Br.; Syahfitri, Dian (Universitas Pendidikan Ganesha, 2018)
This study aims to describe the improvement of speech skills in responding to students' short stories through the application of the stick talking method. This study is based on learning to speak in response to the short story on the students in the category of low. The method used in this study is qualitative descriptive with a classroom action approach that describes speaking skills to respond to classical short stories and speaking skills in response to a short story through a talking stick method. in practive both two cycles consisting of the planning stage, the execution of the action, the observation, and the reflection. The subject of this study were samples dran bypurposive sampling technique of 30 students of class VII-C SMP Negeri 40 Medan. The results showed that students 'ability to respond to the students' short story increased after talking stick method was applied in the pre-cycles, the average score was 52.33 and the percentage of classical completeness was 20% After applying the method of talking stick ), the result of the students 'test scores on the first cycle obtained an average score of 69.5 and increased to 71.67 in the second cycle test.Based on the percentage of students' classical completeness in cycle I 66.67% increase in cycle II 76.67%. The research concluded that the application of talking stick method can improve the speaking skill in responding to the short story in the students of class VII-C SMP Negeri 40 Medan.